INDONESIAN PRIMARY CARE THROUGH UNIVERSAL HEALTH COVERAGE SYSTEMS: A FEELING IN BONES - Asyary, Al (YCAB Publisher & IAKMI SULTRA, 2018)
Jaminan Kesehatan Nasional or JKN realized as the one of problem solving for equity of healthcare in Indonesian setting. At the same point, it has to compatible with all aspects in health financing issues by its newly adopted systems. This review aims to reveal JKN health financing policy since it implemented by 2014 in Indonesia. Several bibliographies databases were identified to conduct literature reviews that comprised of international and national/local journals. It founds that JKN principles focuses on mutual support, not-for-profit, good governance, and portability aspects. JKN enrollment consisted of two types polisholders including incapable polis insurance (PBI JKN) that bear by the Indonesian government, and capable polis insurance (none PBI JKN). JKN have to synergize with recent existing challenges including integration from previous regional health insurance (Jamkesda), healthcare facilities, package benefit, financing issue as well as the deficit issue which happened as lower dues that making by JKN polisholder than the high claim by the healthcare facilities particularly in hospitals. Although, JKN emerges to tackle the inequity of healthcare in all Indonesian regions, the existing settled Jamkesda in several regions, particularly regions with high regional income, made JKN integration as the setback health financing on its regions. Limited healthcare facilities that cooperated with BPJS-Kesehatan also challenged the JKN implementation as well as financial lose in affecting by mismatch between medical expenditures with JKN claimed as per package. It concludes that the political willing to choose several options including to prevent JKN deficit depend on the leader commitment to make JKN as not for another journey but it shall be the destination for health financing in Indonesia.